Distance education courses: the international experience - Шалацька, Ганна Миколаївна (Educational Dimension, 2015)
Shalatska G. M. Distance education courses: the international experience. The article describes the experience of developing a distance course based on the British training platform FutureLearn. Аn analysis of international experience and distance education courses is carried out. An attempt to identify tendencies and ways of introduction the new technologies in training and development the qualification level in the domestic pedagogical practice is made.